Temporal changes in the prevalence of childhood asthma and allergies in urban and rural areas of Cyprus: results from two cross sectional studies - Middleton, Nicos; Kolokotroni, Ourania; Nicolaou, Nicolaos C.; Pipis, Spiros D.; Priftis, Kostas N.; Milton, Donald Kirby; Yiallouros, Panayiotis K. (My University, 2011)
Background: The prevalence of childhood asthma and allergies in Cyprus was significantly higher in urban compared to rural areas back in the year 2000, against a background of an overall low prevalence (e.g. current wheeze 6.9%) by comparison to northern European countries. In this study we aimed to assess temporal changes in the prevalence of asthma and allergies in Cyprus after an 8-year interval and to examine whether any differential changes have occurred in urban and rural parts of the island. Methods. During the academic years 1999-2000 and 2007-2008, the parents of 7-8 year old children residing in the same set of urban and rural areas completed the ISAAC core questionnaire. In addition to providing prevalence estimates of allergic diseases in 2000 and 2008, changes between the two periods were expressed as odds ratios estimated in multiple logistic regression models adjusting for survey participants' characteristics. Results: The prevalence of current wheeze was higher in 2008 (8.7%, 95% confidence interval 7.5%-9.9%, n = 2216) than the previously recorded figure in 2000 (6.9%, 95% CI 6.2%-7.6%, OR = 1.25, 95% CI: 1.02-1.53, n = 4944). Significant increases were also seen in the prevalence of lifetime asthma (11.3% vs. 17.4%, OR = 1.59, CI: 1.36-1.86), eczema (6.8% vs. 13.5%, OR = 1.91, CI: 1.59-2.29) and allergic rhinoconjuctivitis (2.6% vs. 5.2%, OR = 1.82, CI: 1.39-2.41). The prevalence of current wheeze nearly doubled between 2000 and 2008 in rural areas (5.4% vs. 9.7%, OR 1.81, CI: 1.24-2.64) while no significant change was observed in urban areas (7.5% vs. 8.4%, OR 1.08, CI: 0.84-1.37); p value for effect modification = 0.04. Rises in asthma and rhinitis prevalence, but not eczema were also more pronounced in rural compared to urban areas. Conclusions: The prevalence of allergic diseases in Cyprus is still on the rise; recent increases appear more pronounced among children living in rural areas possibly indicating recent environmental and lifestyle changes in these communities.
Keywords: Asthma; Allergens; Allergic sensitization